IRPINIA EARTHQUAKE 23 NOVEMBER 1980 - LESSON FROM NATURE REVILED BY JOINT DATA ANALYSIS - Pulinets S.A.; Biagi P.; Tramutoli V.; Legen'ka A.D.; Depuev V.Kh. (My University, 2007)
A devastating earthquake of magnitude 6.9 occurred in Southern Italy on 23rd November 1980 in Irpinia-Basilicata area. Variations of different geochemical, atmospheric and ionospheric parameters and electromagnetic emissions were registered around the time of the Irpinia earthquake. The substantial progress reached in understanding the physics of the electromagnetic and thermal anomalies associated with the earthquake preparation process permitted us to create the Lithosphere-Atmosphere-Ionosphere (LAI) coupling model published recently. It shows that the observed effects are not independent but present the cause-consequence chain of physical processes and plasma- chemical reactions. We try to analyze the seismic data, radon emanation, hydrological anomalies, ground based ionosondes network, NOAA/AVHRR Thermal Infrared Irradiance (TIR) anomaly, Intercosmos-19 satellite topside sounding and VLF emissions data using the concept of the developed model and existing laboratory and largescale active experiments on air ionization. If the observed radon activity is really connected with the earthquake preparation process, all other variations of the atmosphere and ionosphere parameters can be explained as a consequence of the main physical process air ionization by radon.
Keywords: IONIZATION; LITHOSPHERE-ATMOSPHERE-IONOSPHERE COUPLING; RADON